SECTION 220–SHOULD CORPORATIONS WORRY? - Dohr, J. L. (The Accounting Review, 1928)
Every Federal income and profits tax act discriminates between various classes of taxpayers. The sixteenth amendment of the U.S. Constitution enacted in 1913 imposed a tax of one per cent upon the net income of corporations. Thus, at the very outset, taxpayers were faced with a discrimination, and in all probability many of them took occasion to adjust their financial organizations to meet the discrimination. The U.S. Congress must have foreseen this, for the Act contained a provision imposing an additional tax upon the individual's pro rata share of corporate income which was accumulated beyond reasonable needs of the business for the purpose of preventing the additional tax upon its stockholders. Accordingly, the penalty of Section 220 under this law is imposed upon any corporation which is formed or availed of for the purpose of preventing imposition of surtaxes upon its stockholders. The penalty is fifty per cent of its net income plus dividends, which is a very severe penalty. The article discusses the impact of this penalty for corporations and stockholders in detail.